Examination of the Wear Behavior of Cu-Ni/B4Cp Composite by the Taguchi Method - Yildiz, Tulay; Gur, Ali Kaya; Aba, Suleyman (Carl Hanser Verlag, 2014)
The purpose of this study is to investigate the effects of process parameters on adhesive wear resistance by using the Taguchi experimental design method. In this study, Cu-Ni/B4Cp composites were produced by the powder metallurgy method and the effect on the adhesive wear resistance was investigated. Cu-Ni/B4Cp composite materials were made by cold pressing methods and reinforced with 1 % Ni as well as with 6, 12 and 18 % B4Cp, respectively. The sintering was carried out at 800 and 900 degrees C for 60 minutes. The wear tests were performed by using block on ring test apparatus at loads of 5, 10 and 15 N at a rotation speed of 90 rpm and a wear distance of 250, 500 and 750 m, respectively. The results were evaluated by the calculated wear losses. The wear resistance increased with increasing B4C ratio.
Keywords: Materials testing; Taguchi; ANOVA; Cu-Ni/B4Cp composite; adhesive wear